Financing infrastructure projects based on risk sharing model: Istisna sukuk / Davood Manzoor, Majid Karimirizi and Ali Mostafavisani. - Manzoor, Davood; Karimirizi, Majid; Mostafavisani, Ali (Universiti Teknologi Mara Selangor, 2017)
One of the basic needs of developing countries is the economic infrastructure that is the basis of growth and development in other sectors of the economy. The lack of proper response to financing needs in this sector will result in economic development that faces major challenges anddifficulties. Designing an optimal solution to financing these types of projects is thus, a fundamental need. These projects have two main characteristics that should be considered in the financing method. The first is long-term period to constructing and the second is the high cost of implementation. The use of Islamic financial innovations based on Islamic contracts can meet many of these needs.States in developing countries have so far preferred to raise fund based on debt, ignoring the fact that this kind of financing and choice of method will cause many problems for the economy. Financial crises and economic stability, creating a leverage in the economy, budget deficit, inflation and the distribution of risk among economic agents are the issues that affect the structures and models of financing. Istisna Sukuk has the potential to be used for infrastructure project financing and can be combined with other contracts, including Ijarah and Musharakah, for these types of projects. In this paper, various models are presented and examined to show that by adapting the financial flows of state-owned projects with real economy, especially in the field of infrastructure, the macroeconomic imbalances can be avoided. This is most relevant in the "Istisna-Musharakah-Stock" model.